دراسة أثر بعض المؤشرات السكانية على استهلاك الطاقة الكهربائية في سورية باستخدام بعض الأساليب الإحصائية - أحمد, طالب; اسكندر, إبراهيم (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدف هذا البحث إلى تحديدأهمالمؤشرات السكانية التي تؤثر على استهلاك الطاقة الكهربائية باستخدام أسلوب التحليل العاملي، والاستفادة من العوامل الناتجة في بناء النموذج الرياضي الذي يربط بين العوامل الممثلة لمؤشرات النموالسكانيوالطاقةالكهربائية في سورية باستخدام الانحدار الخطي. وكانت أهم النتائج:تحديد المؤشرات السكانية الخمسة التالية: (عدد السكان، نصيب الفرد من الكهرباء، الاكتظاظ السكاني (الكثافة السكانية)، عدد المشتركين بالتيار الكهربائي، حجم قوة العمل)وتمثيلها في عامل واحد، من خلال نموذج رياضي يمثل المؤشرات السكانية أفضل تمثيل. كما تم التوصل باستخدام أسلوب الانحدار الخطي إلى نموذج رياضي معنوي يمثل أثر (العامل المستخرج) الممثل للمؤشرات السكانية( كمتغير مستقل) على استهلاك الطاقة الكهربائية (كمتغير تابع) في سورية. The objective of the research is to reduce the number of indicators of population growth using the method of factor analysis, and to take advantage of the factors resulting from the application of the method of analysis in the construction of the mathematical model, that links the factors represented by indicators of population growth and electric power in Syria using linear regression. The most important results were: Using the method of factor analysis, we were able to represent the following fifth population growth indicators: number of population, electricity per person, population density, number of participants in power supply, size of work force) in one factor, and we result mathematical model thatrepresentedpopulation growth indicators the best representation. Using a simple linear regression, we result a significant mathematical model that obtained that represents the effect of population growth indicators (as an independent variable) on electric power (as a dependent variable) in Syria.